Discovery of potential therapeutic targets and biomarkers for ischemic stroke by quantitative proteomics - Arnab Datta (2014)
Ischemic stroke resulting from the occlusion of cerebral vasculature is the major cause (around 80%) of stroke. Stroke is the second most common cause of death and the predominant cause of adult morbidity worldwide with limited therapeutic option. Despite decades of intensive research, the translation of hypothesis into effective therapies remains an insurmountable challenge without any success in clinical trials. In addition, despite the advancement of sophisticated clinical imaging, there remains ample scope to improve the diagnosis or prognosis of ischemic stroke. Evaluating the failures of previous clinical trials has resulted in a paradigm shift from a reductionist to a system-wide approach by accommodating the emerging concepts of a neurovascular unit instead of neurons only or from a single target to a multi-target therapy to tackle this multifaceted disease.